CLASSICAL AND QUANTUM DYNAMICS USING COMPUTER SIMULATION - SETIAWATI (NIM 20206026), NELLY
Dynamics, a branch of physics dealing with movement and force, is divided into two sections. They are classical dynamics and quantum dynamics. Basic to any presentation of classical dynamics is Newton second law equation which its solution for certain boundary condition can describe the position, velocity and acceleration of the particle as function of time t. While one of the basics to any presentation of quantum dynamics is Schrodinger equation which its solution gives wave function for a physical system can predict the future behavior of system such as the probability of events, energy levels and expectation value. By using Mathematica 6.0, Schrodinger and Newton second law equation are simulated with some conditions. The solving procedures are defined as some Mathematica Functions. The source code of corresponding programs namely klasik.nb and kuantum.nb are shown in the appendices.